Pueblos y caciques yucatecos, 1550-1580 - Quezada, Sergio (Colegio de México, Centro de Estudios Históricos, 1993)
"Impressive, revised doctoral dissertation that explores the impact of the Spanish presence on indigenous Yucatecan political and territorial institutions. Revisits known primary source material but with new questions and interpretations, and with the intention of defining more precisely the batab, batabil, halach uinic, tzucub, and cuchcabal. Tracks their evolution into colonial entities, such as caciques, pueblos, cacicazgos, and provinces through a critical period of change"--Handbook of Latin American Studies, v. 58.